Alternative tobacco and nicotine products us and its associated factors among late adolescents in government colleges in Kota Bharu - Yusof, Nurul Azreen (2017)
Introduction The rising prevalence of tobacco products use among adolescents nowadays is a matter of concern as tobacco is a well-known cause of various diseases with high morbidity and mortality. This situation is expected to be worsened by the preexisting alternative tobacco products that have been used since the last century and the emergence of newer alternative tobacco and nicotine products (ATNP) in the markets. This study examined the use of e-cigarettes and shisha, as well as the other types of older smoked tobacco such as bidi, kretek, cigars or cigarillo, and smokeless tobacco products among late adolescents. Objective To determine prevalence of alternative tobacco and nicotine products use among late adolescents in government colleges in Kota Bharu and its associated factors. Methodology This is a cross-sectional study involving 388 students from government colleges in Kota Bharu aged 18 to 19 years old. They were requested to answer a set of questionnaire on sociodemographic, types of tobacco and nicotine products use, environmental influence, reasons for using the products, their perceptions towards the products, refusal skills, and self-efficacy. Results The prevalence of alternative tobacco and nicotine products (ATNP) use among the adolescents was 14.4%. Peer use, male sex, cigarette smoking status, and selfefficacy were significantly associated with ATNP use by both simple and multiple logistic regressions. While the other factors such as parental and sibling use, perception that ATNP were less harmful and less addictive, reasons for use such as curiosity, less expensive, to aid smoking cessation, variety of flavours and taste as well as refusal skills were not significant. Conclusion The prevalence of ATNP use among adolescents in Kota Bharu was much higher than what was reported among Malaysian adolescents. Measures should be taken to reduce the influence of peers in tobacco products use and interventions should be focussing more on male adolescents. Prevention of cigarette smoking and strengthening of self-efficacy among adolescents will indirectly reduce ATNP in the future. This issue should be tackled seriously by the government, local authorities who responsible for tobacco control and regulation, health organisations, and schools in combating tobacco and nicotine use among adolescents.